2006
DOI: 10.1084/jem.20061099
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 drives innate and T cell–mediated intestinal inflammation

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract involving aberrant activation of innate and adaptive immune responses. We have used two complementary models of IBD to examine the roles of interleukin (IL)-12 family cytokines in bacterially induced intestinal inflammation. Our results clearly show that IL-23, but not IL-12, is essential for the induction of chronic intestinal inflammation mediated by innate or adaptive immune mechanisms. Depletion of IL-23 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
651
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 744 publications
(682 citation statements)
references
References 60 publications
28
651
0
3
Order By: Relevance
“…However, further studies will be necessary to determine the actual role for TGF-1 and other TGF-1 related cytokines like IL-10 in the course of regulation of gastrointestinal tract inflammation by IL-25. Even though a number of recent studies reported a critical role for IL-23 in the pathogenesis of intestinal inflammation (26,27), the actual causes of elevation of IL-23 cytokine in these DSS-induced colitis mice treated with rIL-25 remain uncertain. However, TGF-1 has been shown to have the ability to up-regulate IL-23R expression to induce IL-23 responsiveness (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies will be necessary to determine the actual role for TGF-1 and other TGF-1 related cytokines like IL-10 in the course of regulation of gastrointestinal tract inflammation by IL-25. Even though a number of recent studies reported a critical role for IL-23 in the pathogenesis of intestinal inflammation (26,27), the actual causes of elevation of IL-23 cytokine in these DSS-induced colitis mice treated with rIL-25 remain uncertain. However, TGF-1 has been shown to have the ability to up-regulate IL-23R expression to induce IL-23 responsiveness (28).…”
Section: Discussionmentioning
confidence: 99%
“…The current view of mouse Th17 development is that TGF␤1 and IL-6 are the key cytokines that initiate the differentiation process and that IL-23 plays an essential role in the expansion and maintenance of this lineage. Support for the notion of an IL-23/IL-17 axis has been provided by a number of models of autoimmunity (6,(8)(9)(10)(11)26,39,(44)(45)(46), but despite these compelling data in mice, a systematic analysis of human Th17 differentiation from naive cells has not yet been undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have supported the notion of a role of IL-23 in autoimmune responses, and a preponderance of evidence indicates that this cytokine may be more clinically relevant than its close relative IL-12 in causing autoimmunity (8)(9)(10)(11)45). The recent discovery of the relationship between IL-23R single-nucleotide polymorphisms and the prevalence of inflammatory bowel disease highlights the relevance of this cytokine in human autoimmune disease (48).…”
Section: Il-17 Regulation In Human T Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, it was demonstrated that adoptive transfer of IL-23-polarized autoantigen-specific Th17 effector cells were able to transfer EAE more effectively than Th1 cells [9]. IL-17 and IL-23 have also been shown to have a role in the pathogenesis of CIA [10] and colitis [11,12]. These studies established a pathogenic role for Th17 cells in organ-specific autoimmune and chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 94%